Pengelolaan dan Pembukuan Keuangan Pada UMKM di Pasar Bengkulu Demi Konsistensi Usaha di Masa Pandemi Covid-19 - Esti Pasaribu; Yefriza Yefriza; Antoni Sitorus (Madani : Indonesian Journal of Civil Society, 2022)
During the pandemic, there are still many people in Pasar Bengkulu Village who do not work, where housewives should be able to use their free time more productively. Based on observations made in Pasar Bengkulu Village, many housewives who have been in the business of selling souvenirs in tourist areas, just don't develop it. Most housewives who have tried small businesses eventually close their businesses. If housewives have clear and systematic financial management and sales bookkeeping skills, then the side business of selling souvenirs that have been carried out so far is expected to run more smoothly and develop. The Master of Applied Economics at the University of Bengkulu conducted Community Service (PKM) activities in Pasar Bengkulu Village, Sungai Serut District, Bengkulu in the period July-November 2021. This PKM succeeded in attracting the interest of 30 activity participants to start implementing financial planning patterns and making business reports so that financial households are getting better and better.